Using visual representations in identifying students' preconceptions in friction. Issue 2 (3rd April 2021) - Canlas, Ian Phil
ABSTRACT: Background : Understanding students' preconceptions is an important initial step towards a successful and meaningful learning in physics. This is more relevant and important especially for concepts that are introduced formally as early as preschool including friction. Visual representation maybe often used as an aid to teaching, however, considering that creating visual representations allows students to make connections between experiences and specific concepts, it may be possible to use the same in revealing and diagnosing students' preconceptions. Purpose : This study attempted to explore the use of visual representations in identifying students' preconceptions in friction. The preconceptions were categorized and compared to those existing in literature. Sample : Using convenience sampling, a total of sixty-two grade 7 students, aged 12–13, from one school that represent the government schools for the gifted participated in the study. These schools follow a trilingual curriculum framework. Design and methods : Following the qualitative descriptive research design, visual representations produced by students prior to a lesson on friction were analyzed using the four-step approach to semiotic analysis of drawings. For verification and confirmation purposes, interviews were conducted. Thematic analysis was performed to identify and categorize the preconceptions. Results : Results revealed that students often associate friction to human activities such as sliding and rolling objects in flat surfaces and are contextual in nature. There exist limited preconceptions as proven with the non-representation of static friction and non-representation of friction at mesoscopic and microscopic levels. There also exist misconception and inconsistent preconception related to determining the direction of friction among sliding and rolling objects. Conclusion : This study shows that using visual representation paired with interview may be an effective and efficient diagnostic assessment alternative for concepts in friction and most likely to concepts that have similar nature to friction.